Halal compliance decisions by food suppliers based on analytic hierarchy process - Iberahim, Hadijah; Mustapha, Nurol’ain; Kamaruddin, Rohana; Abdul Hamid, Norlida; Abu Samah, Mohd Armi (American Scientific Publishers, 2016)
The halal food chain is one of the leading industries that is aggressively adapting to newly emerging consumer interests like food safety, animal welfare and convenience in cooking and eating. Past studies, on tracking movement of imported food products reveals a critical level of non-compliance among halal logistics operators. In extension, this paper aims to review and identify criteria of behavior among halal food suppliers. The study used Analytic Hierarchy Process to provide insights on criteria and sub-criteria that influence food suppliers’ decisions on integrating and complying to halal standard. Exclusive interviews with 12 food suppliers were conducted. This study discovers that suppliers give priority to knowledge on halal, followed by practice, activity and resource. The study proposed that there is a critical need for JAKIM and JAIN, or any halal certification authority in any part of the world, to increase awareness on various issues related to halal standard, halal certification and halal regulation to encourage food suppliers to comply to all requirements in total. Further, it is also knowledge that will increase their integrity to provide food that encapsulate the true concept of Halalan Toyyiban.